Corrigendum to “Integrated miniature fluorescent probe to leverage the sensing potential of ZnO quantum dots for the detection of copper (II) ions” - Sing, Muk Ng; Sing, Derrick Nguong Wong; Hui, Jane Chiun Phung; Suk, Fun Chin; Hong, Siang Chua (Elsevier B.V., 2014)
Quantum dots are fluorescent semiconductor nanoparticles that can be utilised for sensing applications. This paper evaluates the ability to leverage their analytical potential using an integrated fluorescent sensing probe that is portable, cost effective and simple to handle. ZnO quantum dots were prepared using the simple sol-gel hydrolysis method at ambient conditions and found to be significantly and specifically quenched by copper (II) ions. This ZnO quantum dots system has been incorporated into an in-house developed miniature fluorescent probe for the detection of copper (II) ions in aqueous medium. The probe was developed using a low power handheld black light as excitation source and three photo-detectors as sensor. The sensing chamber placed between the light source and detectors was made of 4-sided clear quartz windows. The chamber was housed within a dark compartment to avoid stray light interference. The probe was operated using a microcontroller (Arduino Uno Revision 3) that has been programmed with the analytical response and the working algorithm of the electronics. The probe was sourced with a 12V rechargeable battery pack and the analytical readouts were given directly using a LCD display panel. Analytical optimisations of the ZnO quantum dots system and the probe have been performed and further described. The probe was found to have a linear response range up to 0.45mM (R(2)=0.9930) towards copper (II) ion with a limit of detection of 7.68×10(-7)M. The probe has high repeatable and reliable performance.